PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK MATA PELAJARAN IPS - Alia Ismail; Agil Bahsoan; Yulianti Toralawe; Frahmawati Bumulo; Maya Novrita Dama (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low critical thinking skills and student learning achievement in social studies subjects in formal school environments require the use of innovative student-centered learning models. This descriptive quantitative verification study aims to test the effect of the Problem Based Learning (PBL) model on the critical thinking skills of eighth-grade students of SMP Negeri 1 Telaga. Primary data collection was conducted through Likert scale questionnaires, observation, and documentation to a sample of 48 students selected by proportional sampling from a population of 237 students. Data analysis techniques include the Kolmogorov-Smirnov normality test, simple linear regression, partial t-test, and coefficient of determination analysis via SPSS 20.0. The test results show a regression equation of Y = 16.375 + 0.749X with a normal distribution of data (Kolmogorov-Smirnov Z = 1.081; p = 0.193). The PBL model has been proven to have a positive and significant effect on students' critical thinking based on the calculated t value of 6.375 which exceeds the t table of 1.679 at a significance level of 5 percent (p = 0.000). The coefficient of determination R square value of 0.469 indicates that the PBL model contributes 46.9 percent to the variation in students' critical thinking, while the remaining 53.1 percent is influenced by external factors. The main conclusion proves that the application of PBL syntax is effective in transforming the learning climate and improving students' analytical reasoning and self-regulation independently. ABSTRAK Rendahnya keterampilan berpikir kritis dan ketuntasan belajar siswa pada mata pelajaran IPS di lingkungan sekolah formal menuntut digunakannya model pembelajaran inovatif yang berpusat pada siswa. Penelitian kuantitatif deskriptif verifikatif ini bertujuan menguji pengaruh model Problem Based Learning (PBL) terhadap keterampilan berpikir kritis peserta didik kelas VIII SMP Negeri 1 Telaga. Pengumpulan data primer dilakukan melalui kuesioner skala Likert, observasi, dan dokumentasi kepada sampel 48 siswa yang dipilih secara proportional sampling dari populasi 237 siswa. Teknik analisis data meliputi uji normalitas Kolmogorov-Smirnov, regresi linier sederhana, uji-t parsial, serta analisis koefisien determinasi via SPSS 20.0. Hasil pengujian menunjukkan persamaan regresi Y = 16,375 + 0,749X dengan sebaran data berdistribusi normal (Kolmogorov-Smirnov Z = 1,081; p = 0,193). Model PBL terbukti berpengaruh positif dan signifikan terhadap berpikir kritis siswa berdasarkan nilai t hitung 6,375 yang melebihi t tabel 1,679 pada taraf signifikansi 5 persen (p = 0,000). Nilai koefisien determinasi R square sebesar 0,469 mengindikasikan bahwa model PBL berkontribusi sebesar 46,9 persen terhadap variasi berpikir kritis siswa, sementara 53,1 persen sisanya dipengaruhi faktor luar. Simpulan utama membuktikan bahwa penerapan sintaks PBL efektif mentransformasi iklim belajar serta meningkatkan nalar analitis dan regulasi diri siswa secara mandiri.